2008
DOI: 10.4085/1062-6050-43.4.364
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelationships Among Sex Hormone Concentrations, Motoneuron Excitability, and Anterior Tibial Displacement in Women and Men

Abstract: The observed correlations did not support our hypothesis that the relationships between sex hormone levels and reflex activity or between sex hormone levels and ATD would be different for women compared with men. If sex hormone concentrations significantly contribute to anterior cruciate ligament ruptures because of changes in laxity or in motoneuron excitability, their mechanism of action is likely multifactorial and complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 47 publications
4
29
0
2
Order By: Relevance
“…Nineteen females and thirteen males between the ages of 18 and 35 participated in the study. To be eligible for participation, female participants were required to report having regular menstrual cycles, as defined by a cycle length between 28 and 32 days that varied no more than 3 days, over the previous 3 cycles . Additionally, the female participants were required to report not taking any hormone‐based contraceptives within the year prior to participation in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen females and thirteen males between the ages of 18 and 35 participated in the study. To be eligible for participation, female participants were required to report having regular menstrual cycles, as defined by a cycle length between 28 and 32 days that varied no more than 3 days, over the previous 3 cycles . Additionally, the female participants were required to report not taking any hormone‐based contraceptives within the year prior to participation in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the collection of the H‐reflexes, the electrode sites on the soleus, tibialis anterior, and lateral malleolus were prepped for application of lubricated surface electromyography (EMG) electrodes (Ag/AgCl). The EMG electrodes on the soleus and the tibialis anterior were placed over the muscles longitudinally with an interelectrode distance of 2 cm . The EMG of the evoked responses was sampled at 2000 Hz .…”
Section: Methodsmentioning
confidence: 99%
“…It is apparent that menstrual cycle sex hormones profoundly affect excitability of the central nervous system. Using H-reflexes as a metric for excitability at the spinal level, Hoffman et al (15) demonstrated that there was no change across the menstrual cycle. This indicates that changes in central nervous system excitability likely occur at the cortical and/or subcortical levels.…”
Section: Applied Sciencesmentioning
confidence: 99%
“…Other inclusion criteria were a positive Zohler (Appendix 1) or Clarke sign (Appendix 2), patellar tenderness, and an average pain level in the preceding month of at least 3 on a visual analog scale (VAS) . Additional inclusion criteria were insidious onset of symptoms (nontraumatic), a score of at least 11 on the Persian version of the Functional Index Questionnaire (FIQ), age ≤ 40 years (to reduce the likelihood of osteoarthritic changes), unilateral PFPS, body mass index between 18.5 and 24.9 kg/m 2 , normal menstrual cycle, that is, a self‐reported cycle duration of 22‐36 days with no more than 3 days of variation in cycle length during the previous 3 months, and not using oral contraceptive hormones for 3 months before the start of the study.…”
Section: Methodsmentioning
confidence: 99%